Forced-Air Warming During Pediatric Surgery: A Randomized Comparison of a Compressible With a Noncompressible Warming System. Issue 5 (October 2016) - Triffterer, Lydia; Marhofer, Peter; Sulyok, Irene; Keplinger, Maya; Mair, Stefan; Steinberger, Markus; Klug, Wolfgang; Kimberger, Oliver
Abstract : (Abstracted from Anesth Analg, 122:219–225, 2016) Perioperative active warming is paramount to overcoming the common problem of hypothermia, particularly in pediatric patients. However, the process is often challenging in this particular population.